Analysis of Erosion and Land Conservation Based on Geographic Information System in Way Sekampung Subwatershed - Azzahra, Arrum; Andawayanti, Ussy; Asmaranto, Runi (Fakultas Teknik Universitas Brawijaya, 2024)
Way Sekampung subwatershed is the watershed area of Way Sekampung dam. The changes in land use that occurred in the Way Sekampung subwatershed caused flooding and landslides. To reduce existing problems, vegetative and mechanical land conservation efforts are needed. In this study, the USLE method was used to estimate the rate of erosion and then map the distribution of the Erosion Hazard Index in the Way Sekampung Subwatershed with the help of Geographic Information System (GIS). Based on existing conditions, the erosion rate in 2017 was 29626.262 tons/ha/year; in 2022, the erosion rate was 76617.579 tons/ha/year. The results of the analysis of the Erosion Hazard Index in 2017 and 2022 showed four criteria, namely low with a difference of -1.115%, moderate with an increase of 1.140%, high with a difference of -0.097%, and very high with a difference of 0.071%. Conservation with new land use, construction of terraces, and check dams has resulted in a reduction in erosion in the Way Sekampung Subwatershed with an Erosion Hazard Index, which is a low index increase of 26.992% from the existing condition and a very high 22.819% reduction from the existing condition. These results show that land conservation can reduce erosion in the Way Sekampung Subwatershed.